A function of Bioslurry Organic for Solid Fertilizer - Dewi, Intan Suksma; Kusuma, Maritha Nilam; Pramestyawati, Talentnia (Institut Teknologi Adhi Tama Surabaya, 2020)
Indonesia is an agricultural country in which people mostly work as farmers and produce abundant farming outcomes. On one hand, the use of chemical fertilizer supports the plants growing well. On the other hand, it decreases the soil fertility and farming product quality. The alternative way to reduce or substitute the chemical fertilizer is by using organic fertilizer which can be made through composting method for 2 months mixing the leaf waste and rice straw. Before mixing both materials, the values of C, N, P, K and the water content of Bioslurry were respectively 15.17%, 0.27%, 0.3%, 0.05%, and 67.07%. Meanwhile, the values of C, N, P, K and the water content of leaf waste were consecutively 41.12%; 1.22%; 1.16%; 8.94%; and 28.77%. Moreover, the values of C, N, P, K, and the water content of rice straw were sequentially 39.42%; 1.20%; 1.05%; 10.07%; and 31.23%. After mixing both materials through composting method, the results of rice straw fertilizer got C-Organic 20.87%; N 2.01%; P 0.16%; K 5.64%; water 22.31%, and C/N ratio 16.38%. Meanwhile, the composting process of leaf waste yielded C-Organic 25.44%; N 1.18%; P 0.18%; K 7.95%; water 11.85%, and C/N ratio 21.55%.